Characteristics of flow and heat transfer of nanofluids under laminar states. (2nd January 2018) - Wang, Yuyan; Wang, Peng; Yoon, Sungmin; Yu, Yuebin; Bai, Minli
ABSTRACT: The current article used four different models (single-phase, Mixture, Eulerian, and discrete phase model) to investigate the flow and heat transfer characteristics of nanofluids under a laminar state. We explored the Al2 O3 -water nanofluid inside a microscale trapezoidal channel and the CuO-oil inside a circular channel with a regular size. The velocity and temperature fields of nanofluids were discussed by comparing the differences among each model. It is revealed that the change of flow characteristics of nanofluid plays a more decisive role in its heat transfer enhancement besides the improvement of its physical properties.